PENGARUH PROSEDUR PELAYANAN DAN KEMAMPUAN PEGAWAI TERHADAP KUALITAS PELAYANAN AKTA NIKAH (NON-MUSLIM) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN JOMBANG - Hidayat, Ujang; Astuti, Retno Sunu (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2018)
The background of this study is the increase in a number of marriage certificate applications (Non-Muslim) in Jombang Regency. This increase in the number of applicants must be balanced with the qualified service of marriage certificates at the Civil Registry Office of Jombang Regency. However, if the increase in the number of applicants for marriage certificates is compared to the applicants for the birth certificate, the number of applicants for the marriage certificate is very little than the number of applicants for the birth certificate. With the small number of applicants for marriage certificates, the researcher wants to know whether the marriage certificate service at the Civil Regency Office of Jombang Regency is good or not. To find out whether the marriage certificate service is qualified or not, the researcher chooses two research variables, which are service procedures and employee capabilities. The purpose of this study is to determine the influence of service procedure and the capability of employee variables on the quality of marriage certificate services at the Civil Registry Office in Jombang Regency. The researcher conducts literature studies, compiled hypotheses, and searches for data as many as 100 respondents using non-probability sampling technique. Furthermore, the researcher analyzes the obtained data using linear regression analysis and multiple regression including the validity and reliability test, Spearman correlation, simple linear regression, multiple linear regression, and hypothesis testing using t-test and F test. F test explains how big the influence of service procedure and the capability of employeevariables on the quality of marriage certificate services.